2021
DOI: 10.1557/s43578-021-00239-w
|View full text |Cite
|
Sign up to set email alerts
|

Showerhead-assisted chemical vapor deposition of CsPbBr3 films for LED applications

Abstract: CsPbBr3 represents a highly attractive material for perovskite light-emitting diodes (PeLEDs) in the green spectral range. However, the lack of deposition tools for reproducible and scalable growth of perovskite films is one of the major obstacles hindering PeLED commercialization. Here, we employ the highly scalable showerhead-assisted chemical vapor deposition (CVD) method to produce uniform pinhole-free CsPbBr3 films for PeLED application. The precursors CsBr and PbBr2 are evaporated under low vacuum in N2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Meanwhile, some other excess electrons accumulate at the HTL/EML interface (Figure 1d), which leads to increased nonradiative recombination. [ 41 ] Hence, in operational PeLEDs, exciton formation in the PVK or accumulation at the interface suggests electron leakage, that is, electron transfer from the perovskites to the PVK or the interface, causing reduced efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, some other excess electrons accumulate at the HTL/EML interface (Figure 1d), which leads to increased nonradiative recombination. [ 41 ] Hence, in operational PeLEDs, exciton formation in the PVK or accumulation at the interface suggests electron leakage, that is, electron transfer from the perovskites to the PVK or the interface, causing reduced efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The PeLED (Device-I) shows relatively poor performance with a maximum EQE of 17.08% and a maximum current density (CE) of 75.40 cd A −1 (Figure 1a; Figure S2a, Supporting Information), which is almost consistent with the literature reports. [38][39][40][41] We built hole-only and electronic-only devices to understand the charge carrier transport properties. The current density-voltage curves (Figure S2b-d, Supporting Information) were analyzed by the Mott-Gurney and Poole-Frenkel laws (details in Supporting Information) to obtain the field-dependent charge carrier mobilities, which demonstrate that the electrons (Figure 1b) show much higher carrier mobility than the holes.…”
Section: Origin Of Efficiency Loss In Nio X -Based Peledsmentioning
confidence: 99%
“…A simplified flow diagram of CVD is shown in Figure a. [ 55 ] In a typical setup, CVD is performed in a tube furnace with strict control of temperature, gas environment, and flow rate. Two gas streams loaded with evaporation precursors are impinged vertically and combined in a static forced mixing unit, with a high‐temperature exhaust system to prevent unwanted deposition during the heating and cooling stages.…”
Section: Strategies For Vacuum Processed Peledsmentioning
confidence: 99%
“…A highly scalable showerhead‐assisted CVD method was applied to produce uniform pinhole‐free CsPbBr 3 films for LED applications by Sanders et al [ 55 ] As shown in the SEM images in Figure 7d, all CVD layers are entirely closed, which is necessary to prevent short circuits in the PeLED stack. Unlike solution processing, the CVD process does not require any pretreatment, thus providing greater flexibility in the choice of novel electrode substrates and charge carrier transport films for PeLEDs.…”
Section: Strategies For Vacuum Processed Peledsmentioning
confidence: 99%
See 1 more Smart Citation